Hemolytic disease and reticulocytopenia of the newborn attributable to maternal immunoglobulin G anti‐M reacting optimally at cold temperatures. Issue 3 (14th January 2021) - Andersen, Lezlie H.; Jacob, Eapen K.; McThenia, Sheila S.; Tauscher, Craig D.; Patterson, Emily R.; Oliveira, Jennifer L.; Rodriguez, Vilmarie
Abstract: Background: Hemolytic disease of the fetus and newborn (HDFN) attributable to anti‐M is rare, although case reports implicate anti‐M in varying severities of HDFN, including fetal hydrops and intrauterine death. Case Description: We describe the case of a newborn with HDFN associated with an atypical immunoglobulin (Ig) G anti‐M that reacted best at cold temperatures. The maternal antibody detected in pregnancy was not reactive at 37°C, and a direct antiglobulin test (DAT) on red blood cells (RBCs) from the newborn was negative, suggesting an anti‐M that should not have been clinically relevant. However, the infant developed hyperbilirubinemia (bilirubin level, 17.6 mg/dL), hemolytic anemia (hemoglobin nadir, 5.5 g/dL), and reticulocytopenia. Laboratory testing demonstrated the presence of an IgG anti‐M in maternal and neonatal samples reacting best at 4°C. This passively acquired IgG anti‐M provoked hemolytic anemia in the infant and likely suppressed erythropoiesis, resulting in reticulocytopenia with prolonged anemia. He was treated for IgG anti‐M HDFN with 10 intravenous Ig infusions and 10 days of oral prednisone followed by a taper. He required seven transfusions with M− RBCs. His hemoglobin level normalized at 3 months of age. Follow‐up at 2 years revealed no hematologic or neuro‐developmental concerns. Conclusion: To our knowledge, this is the second report of HDFN attributable to an IgG anti‐M reacting preferentially at cold temperature with no 37°C reactivity. Clinically relevant IgG anti‐M may elude standard testing. Early recognition and testing for cold‐reacting IgG anti‐M should be considered for newborns with hemolysis, a negative DAT, and prolonged anemia.